A multi-channel model for an a plus 6He nucleus cluster - Amos, K.; Canton, L.; Fraser, Paul; Karataglidis, S.; Svenne, J.; van der Knijff, D. (Springer New York LLC, 2017)
© 2017, SIF, Springer-Verlag Berlin Heidelberg. A multi-channel algebraic scattering (MCAS) method has been used to solve coupled sets of Lippmann-Schwinger equations for the a+ 6 He cluster system, so finding a model spectrum for 10 Be to more than 10MeV excitation. Three states of 6 He were included and the resonance character of the two excited states taken into account in finding solutions. A model Hamiltonian has been found that gives very good agreement with the known bound states and with some low-lying resonances of 10 Be. More resonance states are predicted than those which have been observed as yet. The method also yields S -matrices which we have used to evaluate low-energy 6 He - a scattering cross sections. Reasonable reproduction of low-energy differential cross sections and of energy variation of cross sections measured at fixed scattering angles have been found. Enlarging the channel space by including two higher energy states of 6 He , assuming values for their spin-parities, leads to an enlarged spectrum for 10 Be in which the number and distribution of resonances show similarity to the known spectrum.